2018
DOI: 10.3389/fneur.2018.00752
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Basis of State-Dependent Activity of Upper Airway Muscles

Abstract: Obstructive Sleep Apnea (OSA) is a common sleep-related respiratory disorder that is associated with cognitive, cardiovascular, and metabolic morbidities. The major cause of OSA is the sleep-related reduction of upper airway muscle tone that leads to airway obstructions in individuals with anatomically narrow upper airway. This reduction is mainly due to the suppressant effect of sleep on hypoglossal motoneurons that innervate upper airway muscles. The hypoglossal motoneurons have state-dependent activity, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 104 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…The main results of heart rate variability (HRV) analyses according to the three groups of children and schematic representation of the hypothesis. The upper part of the figure is schematics of brainstem sympathetic nervous system (SNS) and parasympathetic nervous system (PNS: the muscarinic receptors mediate a presynaptic cholinergic inhibition of excitatory glutamatergic transmission to hypoglossal motoneurones) projecting to hypoglossal motoneurones (based on Figure 1 in RukhadzeI & Fenik (2018): left panel: the location of brainstem noradrenergic neurones and cholinergic neurones that project to the hypoglossal nucleus shown on sagittal representation of a rodent brainstem; right panel: a coronal medullary section of a rat brain showing the choline acetyltransferase‐stained motoneurones in the hypoglossal motor nucleus (XII), the dorsal motor nucleus of the vagus (X) and the nucleus of ambiguus, and with part of the paths regulating innervation of the heart), while the lower part (four panels) of the figure is the main results of HRV analyses. Four indices of HRV are described (box and whisker plots show median, 25th and 75th percentiles, and 10th and 90th percentiles); they belong to the oscillatory domain (low frequency/high frequency [LF/HF] ratio), the amplitude domain (HFa and LFa) and the pulse domain (Heart Rate: upper panel).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main results of heart rate variability (HRV) analyses according to the three groups of children and schematic representation of the hypothesis. The upper part of the figure is schematics of brainstem sympathetic nervous system (SNS) and parasympathetic nervous system (PNS: the muscarinic receptors mediate a presynaptic cholinergic inhibition of excitatory glutamatergic transmission to hypoglossal motoneurones) projecting to hypoglossal motoneurones (based on Figure 1 in RukhadzeI & Fenik (2018): left panel: the location of brainstem noradrenergic neurones and cholinergic neurones that project to the hypoglossal nucleus shown on sagittal representation of a rodent brainstem; right panel: a coronal medullary section of a rat brain showing the choline acetyltransferase‐stained motoneurones in the hypoglossal motor nucleus (XII), the dorsal motor nucleus of the vagus (X) and the nucleus of ambiguus, and with part of the paths regulating innervation of the heart), while the lower part (four panels) of the figure is the main results of HRV analyses. Four indices of HRV are described (box and whisker plots show median, 25th and 75th percentiles, and 10th and 90th percentiles); they belong to the oscillatory domain (low frequency/high frequency [LF/HF] ratio), the amplitude domain (HFa and LFa) and the pulse domain (Heart Rate: upper panel).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple neurotransmitters have been implicated in the control of hypoglossal motoneurone activity across the sleep–wake states. However, withdrawal of noradrenergic excitation and cholinergic inhibition essentially contribute to the depression of hypoglossal motoneurone activity during sleep (RukhadzeI & Fenik, 2018). Active muscarinic inhibition mediates pharyngeal hypotonia, particularly during rapid eye movement (REM) sleep (Grace et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In healthy individuals, the airway is kept open by the muscle tone of the genioglossus, palatal, and associated muscles of the throat (3). Those affected by OSA suffer from reduced muscle tone due to suppression of upper airway motoneurons (4). Sleep naturally suppresses these motoneurons, but neuromodulation also plays a role (4).…”
Section: Main Textmentioning
confidence: 99%
“…Those affected by OSA suffer from reduced muscle tone due to suppression of upper airway motoneurons (4). Sleep naturally suppresses these motoneurons, but neuromodulation also plays a role (4). Common symptoms of individuals suffering from OSA include snoring and silent pauses in breathing (5).…”
Section: Main Textmentioning
confidence: 99%
“…Hypoglossal motoneurons (HMNs), which control upper airway muscles, are regulated differently than the spinal motor neurons in REM sleep. Work by several groups has concluded that HMNs are inhibited by a combination of monoaminergic disfacilitation and cholinergic inhibition (Horner et al, 2014;Kubin, 2016;Rukhadze and Fenik, 2018).…”
Section: Introductionmentioning
confidence: 99%